Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557310
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the design and fabrication of physical visualizations

Abstract: Figure 1. Physical visualizations created with our fabrication tool, MakerVis: a) a layered scatterplot modeled after Rosling ; b) a prism map showing relative happiness in US states computed from Twitter sentiments; c), d), e) layered bar charts and line charts crafted by end users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 25 publications
(38 reference statements)
0
29
0
Order By: Relevance
“…Early on, Vande Moere and colleagues pointed out the potential of data sculptures as a medium and the need to study them more deeply [43,75,79]. Later, several papers were published in Visualization and HCI venues that investigate empirical [34], design [67,69], and conceptual [32,33,75,79] questions regarding physicalizations, as well as specific application domains [68]. However, the physicalizations investigated are static and none of this work involves novel input and output technologies.…”
Section: Examples Of Data Physicalization Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Early on, Vande Moere and colleagues pointed out the potential of data sculptures as a medium and the need to study them more deeply [43,75,79]. Later, several papers were published in Visualization and HCI venues that investigate empirical [34], design [67,69], and conceptual [32,33,75,79] questions regarding physicalizations, as well as specific application domains [68]. However, the physicalizations investigated are static and none of this work involves novel input and output technologies.…”
Section: Examples Of Data Physicalization Researchmentioning
confidence: 99%
“…Research has already demonstrated the process for composing and creating one-off static physicalizations using fabrication technologies [68,69]. Dynamic physicalizations, on the other hand, require computer-driven control of physical geometry or of material properties.…”
Section: Enabling Technologiesmentioning
confidence: 99%
See 3 more Smart Citations